Home » vectors » Page 2

Tag: vectors

Prove some vector identities using the “cab minus bac” formula

In the previous exercise (Section 13.14, Exercise #9) we proved the “cab minus bac” formula:

    \[ A \times (B \times C) = (C \cdot A) B - (B \cdot A) C. \]

Using this formula prove the following identities:

  1. (A \times B) \times (C \times D) = (A \times B \cdot D)C - (A \times B \cdot C) D.
  2. A \times (B \times C) + B \times (C \times A) + C \times (A \times B) = O.
  3. A \times (B \times C) = (A \times B) \times C if and only if B \times (C \times A) = O.
  4. (A \times B) \cdot (C \times D) = (B \cdot D)(A \cdot C) - (B \cdot C)(A \cdot D).

  1. Proof. Using the cab minus bac formula with A \times B in place of A, C in place of B, and D in place of C we have

        \begin{align*}  (A \times B) \times (C \times D) &= (D \cdot (A \times B))C - (C \cdot (A \times B))D \\  &= (A \times B \cdot D) C - (A \times B \cdot C) D. \qquad \blacksquare \end{align*}

  2. Proof. Applying the cab minus back formula to each of the three terms in the sum we have

        \begin{align*}  A \times (B \times C) &= (C \cdot A) B - (B \cdot A)C \\  B \times (C \times A) &= (A \cdot B) C - (C \cdot B)A \\  C \times (A \times B) &= (B \cdot C) A - (A \cdot C)B. \end{align*}

    So, putting these together we have

        \begin{align*}  A &\times (B \times C) + B \times (C \times A) + C \times (A \times B) \\  &= (C \cdot A)B - (B\cdot A)C + (A \cdot B)C - (C \cdot B)A + (B \cdot C)A - (A \cdot C)B \\  &= O. \qquad \blacksquare \end{align*}

  3. Proof. From cab minus bac we have

        \[ A \times (B \times C) = (C \cdot A)B - (B \cdot A)C. \]

    Furthermore, since (A \times B) \times C = -C \times (A \times B), we can apply bac minus cab to get

        \begin{align*}  (A \times B) \times C &= -C \times (A \times B) &(\text{Thm 13.12(a)}) \\  &= - ((B \cdot C)A - (A \cdot C) B) \\  &= (A \cdot C)B - (B \cdot C)A \\  &= (C \cdot A)B - (B \cdot C)A + (A \cdot B)C - (A \cdot B)C \\  &= (C \cdot A)B - (B \cdot A)C + B \times (C \times A) \\  &= A \times (B \times C) + B \times (C \times A). \end{align*}

    Therefore,

        \[ (A \times B) \times C = A \times (B \times C) \iff B \times (C \times A) = O. \qquad \blacksquare\]

  4. Proof. From a previous exercise (Section 13.14, Exercise #7(d)) we know the identity A \cdot B \times C = C \cdot A \times B. In this case we have A \times B in place of A, C in place of B and D in place of C. This gives us

        \begin{align*}  (A \times B) \cdot (C \times D) &= D \cdot ((A \times B) \times C)\\  &= ((A \times B) \times C) \cdot D \\  &= (-C \times (A \times B)) \cdot D \\  &= (-(B \cdot C)A + (A \cdot C)B) \cdot D \\  &= (B \cdot D)(A \cdot C) - (B \cdot C)(A \cdot D). \qquad \blacksquare \end{align*}

Prove the “cab minus bac” formula

The “cab minus bac” formula is the vector identity

    \[ A \times (B \times C) = (C \cdot A)B - (B \cdot A)C. \]

Let B = (b_1, b_2, b_3) and C = (c_1, c_2, c_3). Prove that

    \[ \mathbf{i} \times (B \times C) = c_1 B - b_1 C. \]

This is the “cab minus bac” formula in the case A = \mathbf{i}. Prove similar formulas for the special cases A = \mathbf{j} and A = \mathbf{k}. Put these three results together to prove the formula in general.


Proof. For the case A = \mathbf{i} we have

    \begin{align*}  \mathbf{i} \times (B \times C) &= \mathbf{i} \times (b_2 c_3 - b_3 c_2, b_3 c_1 - b_1 c_3, b_1 c_2 - b_2 c_1) \\  &= (0, -b_1 c_2 + b_2 c_1, b_3 c_1 - b_1 c_3) \\  &= c_1 B - b_1 C. \end{align*}

Similarly, for A = \mathbf{j} and A = \mathbf{k} we have

    \begin{align*}  \mathbf{j} \times (B \times C) &= \mathbf{j} \times (b_2 c_3 - b_3 c_2, b_3 c_1 - b_1 c_3, b_1 c_2 - b_2 c_1) \\  &= (b_1 c_2 - b_2 c_1, 0, -b_2 c_3 + b_3 c_2) \\  &= c_2 B - b_2 C \\  \mathbf{k} \times (B \times C) &= \mathbf{k} \times (b_2 c_3 - b_3 c_2, b_3 c_1 - b_1 c_3, b_1 c_2 - b_2 c_1) \\  &= (-b_3 c_1 + b_1 c_3, b_2 c_3 - b_3 c_2, 0) \\  &= c_3 B - b_3 C. \end{align*}

So, if A = a_i \mathbf{i} + a_2 \mathbf{j} + a_3 \mathbf{k} is any vector in \mathbb{R}^3 then we have

    \begin{align*}  A \times (B \times C) &= a_1 \mathbf{i} \times (B \times C) + a_2 \mathbf{j} \times (B \times C) + a_3 \mathbf{k} \times (B \times C) \\  &= a_1 (c_1 B - b_1 C) + a_2 (c_2 B - b_2 C) + a_3 (c_3 B - b_3 C) \\  &= (a_1 c_1 + a_2 c_2 + a_3 c_3) B - (a_1 b_1 + a_2 b_2 + a_3 b_3) C \\  &= (A \cdot C)B - (A \cdot B) C. \qquad \blacksquare \end{align*}

Find vectors which satisfy given relations

  1. Find all of the vectors a \mathbf{i} + b \mathbf{j} + c \mathbf{k} which satisfy

        \[ (a \mathbf{i} + b \mathbf{j} + c \mathbf{k}) \cdot \mathbf{k} \times (6 \mathbf{i} + 3 \mathbf{j} + 4 \mathbf{k}) = 3. \]

  2. Find the shortest length vector a \mathbf{i} + b \mathbf{j} + c \mathbf{k} which satisfies the relation in part (a).

  1. We can compute,

        \begin{align*}  && (a \mathbf{i} + b \mathbf{j} + c \mathbf{k}) \cdot ((0,0,1) \times (6,3,4)) &= 3 \\  \implies && (a,b,c) \cdot (-3,6,0) &=3 \\  \implies && -3a + 6b &= 3 \\  \implies && a &= 2b-1. \end{align*}

    So, b,c can take any value, and then we must have a = 2b-1 for the relation to be satisfied. Therefore, any vector

        \[ (2b-1) \mathbf{i} + b \mathbf{j} + c \mathbf{k} \]

    satisfies the relations.

  2. So, we know the vectors satisfying the relation are of the form (2b-1)\mathbf{i} + b \mathbf{j} + c \mathbf{k}. This means we want to minimize

        \[ (2b-1)^2 + b^2 + c^2 = 5b^2 -4b + 1 + c^2. \]

    This is minimal when c = 0 (since c^2 > 0 for any other value of c). Then we want to find the value of b which minimizes 5b^2 - 4b + 1. Taking the derivative and setting it equal to 0 we have

        \[ 10b - 4 =  0 \qquad \implies \qquad b = \frac{2}{5} \quad \implies \quad a = -\frac{1}{5}. \]

    Hence, the vector of minimal length which satisfies the given relation is

        \[ -\frac{1}{5} \mathbf{i} + \frac{2}{5} \mathbf{j}. \]

Prove statements about a vector satisfying a given vector equation

Consider unit length, orthogonal vectors A,B \in \mathbb{R}^3, and a vector P such that

    \[ P \times B = A-P. \]

Prove the following.

  1. P and B are orthogonal and the length of P is \frac{1}{2} \sqrt{2}.
  2. The vectors P,B,P \times B form a basis for \mathbb{R}^3.
  3. (P \times B) \times B = -P.
  4. P = \frac{1}{2}A - \frac{1}{2} (A \times B).

  1. Proof. We compute,

        \begin{align*}  P \times B = A - P && \implies && B \cdot (P \times B) &= B \cdot A - B \cdot P \\  && \implies && 0 = B \cdot P \end{align*}

    since B \cdot (P \times B) = 0 and B \cdot A = 0 since A and B are orthogonal by assumption. Thus, B and P are orthogonal. Next,

        \begin{align*} \lVert P \times B \rVert^2 &= \lVert P\rVert^2 \lVert B \rVert^2 - (P \cdot B)^2 \\  &= \lVert P \rVert^2 \end{align*}

    since \lVert B \rVert^2 = 1 by hypothesis and P \cdot B = 0. Hence, from the vector equation we have

        \begin{align*}  P \times B = A - P && \implies && \lVert P \times \rVert^2 &= \lVert A-P \rVert^2 \\  && \implies && \lVert P \rVert^2 &= \lVert A \rVert^2 - \lVert P \rVert^2 \\  && \implies && 2 \lVert P \rVert^2 &= \lVert A \rVert^2 \\  && \implies && 2 \lVert P \rVert^2 &= 1 \\  && \implies && \lVert P \rVert^2 &= \frac{1}{2} \\  && \implies && \lVert P \rVert &= \frac{\sqrt{2}}{2}. \qquad \blacksquare \end{align*}

  2. Proof. Since P and B are orthogonal (part (a)), we know the vectors P,B, P \times B are independent. Thus, they form a basis for \mathbb{R}^3 since any three independent vectors in \mathbb{R}^3 are a basis. \qquad \blacksquare
  3. Proof. We compute, the vector (P \times B) \times B is given by

        \[ (p_2 b_3 - p_3 b_2, p_3 b_1 - p_1 b_3, p_1 b_2 - p_2 b_1) \times B. \]

    Then the three coordinates of this cross product are given by

        \begin{align*}  &(p_3 b_1 - p_1 b_3)b_3 - (p_1 b_2 - p_2 b_1)b_2 \\  &(p_1 b_2 - p_2 b_1)b_1 - (p_2 b_3 - p_3 b_2)b_3 \\  &(p_2 b_3 - p_3 b_2)b_2 - (p_3 b_1 - p_1 b_3)b_1. \end{align*}

    Expanding these out we obtain the coordinates

        \begin{align*}  &p_3 b_1 b_3 - p_1 b_3^2 - p_1 b_2^2 + p_2 b_1 b_2 \\  &p_1 b_1 b_2 - p_2 b_1^2 - p_2 b_3^2 + p_3 b_2 b_3 \\  &p_2 b_2 b_3 - p_3 b_2^2 - p_3 b_1^2 + p_1 b_1 b_3. \end{align*}

    Since \lVert B \rVert = 1 we know b_1^2 + b_2^2 + b_3^2 = 1 and since P \cdot B = 0 we know p_1 b_1 + p_2 b_2 + p_3 b_3 = 0. So, simplifying the expressions above, for each of the coordinates we have

        \begin{align*}  p_3 b_1 b_3 - p_1 b_3^2 - p_1 b_2^2 + p_2 b_1 b_2 &= p_3 b_1 b_3 - p_1 (1-b_1^2) + p_2 b_1 b_2 \\   &= p_3 b_1 b_3 - p_1 + p_1 b_1^2 + p_2 b_1 b_2 \\  &= b_1(p_3 b_3 + p_1 b_1 + p_2 b_2) - p_1 \\  &= -p_1 \\[9pt]  p_1 b_1 b_2 - p_2 b_1^2 - p_2 b_3^2 + p_3 b_2 b_3 &= p_1 b_1 b_2 - p_2 (1-b_2^2) + p_3 b_2 b_3 \\  &= p_1 b_1 b_2 - p_2 + p_2 b_2^2 + p_3 b_2 b_3 \\  &= b_2(p_1 b_1 + p_2 b_2 + p_3 b_3) - p_2 \\  &= -p_2 \\[9pt]  p_2 b_2 b_3 - p_3 b_2^2 - p_3 b_1^2 + p_1 b_1 b_3 &= p_2 b_2 b_3 - p_3 (1-b_3^2) + p_1 b_1 b_3 \\  &= p_2 b_2 b_3 - p_3 + p_3 b_3^2 + p_1 b_1 b_3 \\  &= b_3 (p_2 b_2 + p_3 b_3 + p_1 b_3) - p_3 \\  &= -p_3. \end{align*}

    Hence, we indeed have

        \[ (P \times B) \times B = (-p_1, -p_2, -p_3)  = -P. \qquad \blacksquare \]

  4. Proof. We compute

        \begin{align*}  (P \times B) \times B = -P && \implies && (A-P) \times B &= -P \\  && \implies && (A \times B) - (P \times B) &= -P \\  && \implies && (A \times B) - A + P &= -P \\  && \implies && -2P &= (A \times B) - A \\  && \implies && P &= \frac{1}{2}A - \frac{1}{2}(A \times B). \qquad \blacksquare \end{align*}

Prove some facts about vectors in R3

  1. Prove that A,B,C \in \mathbb{R}^3 are all on the same line if and only if

        \[ (B -A) \times (C -A) = O. \]

  2. For two vectors A,B with A \neq B, prove that the line through A and B is the set of all vectors P such that (P-A) \times (P-B) = O.

  1. Proof. Assume A,B,C \in \mathbb{R}^3 all lie on a line L, and let A = (a_1, a_2, a_3), \ B = (b_1,  b_2, b_3), \ C = (c_1, c_2, c_3). Then

        \[ L = \{ A + tB \} \quad \implies \quad C = (a_1 + tb_1, a_2 + tb_2, a_3 + tb_3). \]

    So, we have

        \[ B - A = (b_1 - a_1, b_2 - a_2, b_3 - a_3), \qquad C - A  = (tb_1, tb_2, tb_3). \]

    Thus, (B-A) \times (C-A) is the vector

        \begin{align*}  &((b_2 - a_2)tb_3 - (a_3-b_3)tb_2, (a_3 - b_3)tb_1 - (a_1-b_1)tb_3, (a_1 - b_1)tb_2 - (a_2 - b_2)tb_1) \\  &= (0,0,0). \end{align*}

    Conversely, assume (B-A) \times (C-A) = O. From Theorem 13.12(g) we know this is the case if and only if the vectors B-A and C-A are linearly dependent. Hence, there are nonzero s,t such that

        \[ s(B-A) + t(C-A) = O \]

    Since t is nonzero we may divide by t, and we obtain

        \[ sB - sA + tC - tA = O \quad \implies \quad C = A + \frac{s}{t}(A-B). \]

    But this means C is on the line passing through A and B. \qquad \blacksquare

  2. Proof. If A \neq B, then we know there is a unique line passing through A and B, say

        \[ L = \{ A + t(B-A) \}. \]

    Thus, any point P \in L is given by

        \[ P = (a_1 + t(b_1 - a_1), a_2 + t(b_2 - a_2), a_3 + t(b_3 - a_3) \}. \]

    Therefore, we have

        \begin{align*}  (P-A) \times (P-B) &= t(b_1 - a_1, b_2 - a_2, b_3 - a_3) \times (1-t)(a_1 - b_1, a_2 - b_2, a_3 - b_3) \\  &= t(B-A) \times (B-A) - t(B-A) \times (B-A) \\  &= O. \qquad \blacksquare \end{align*}